Reorganization of microtubules in V-79 cells after treatment with cytohalasin B - Iglič, Aleš (Radiology and oncology (Ljubljana), 1999)
Background. The aim of this work was to study the configuration of the microtubules in the cytochalasin B treated V-79 cells in connection to the cell shape and to see whether there are any similarities to the phenomena taking place in phospholipid vesicles. Subjects and methods. An experiment wasperformed where cytochalasin B was added to the V-79 cells (lung fibroblasts of Chinese hamster). Results. The cell shape changed from an elongated one into the shape with a profile resembling the Greek letter phi. The microtubules were found to be organized into a rod within the symmetry axis of the cell. Conclusion. As similar shapes were previously observed also in the phospholipid vesicles with entrapped microtubule rods, our results support the hypothesis that similar physical mechanisms may pertain in simple systems as well as in living cells.
Keywords: Cells, cultured; Cytochalasin b; Drug effects; Fibroblasts; Microtubules